A response surface methodology approach to improve nitrogen use efficiency in maize by an optimal mycorrhiza-to-Bacillus co-inoculation rate - Ganugi, Paola; Fiorini, Andrea; Rocchetti, Gabriele; Bonini, Paolo; Tabaglio, Vincenzo; Lucini, Luigi (Frontiers in Plant Science, 2022)
Co-inoculation of Arbuscular Mycorrhizal Fungi (AMF) and bacteria can be synergic and potentially increase nitrogen use efficiency (NuE) in plants, thus reducing nitrogen (N) fertilizers use and their environmental impact. However, limited research is available on AMF-bacteria interaction and the definition of synergisms or antagonistic effects is unexplored. In this study, we adopted a Response Surface Methodology (RSM) to assess the optimal combination of AMF (Rhizoglomus irregulare and Funneliformis mosseae) and Bacillus megaterium (a PGPR - Plant Growth Promoting Rhizobacteria) formulations to maximize agronomical and chemical parameters linked to N utilization in maize (Zea mays L.). The fitted mathematical models, as well as 3D response surface and contour plots, allowed us to determine the optimal AMF and bacterial doses, which approximately accord to 2.1 kg ha-1 of both formulations. These levels provided the maximum values of SPAD, aspartate and glutamate. On the contrary, agronomic parameters were not affected, excepting for the nitrogen harvest index (NHI), which was slightly affected (p-value<0.10) and indicated a higher N accumulation in grain following inoculation with 4.1 and 0.1 kg ha-1 of AMF and B. megaterium, respectively. Nonetheless, the identification of saddle points for asparagine and the tendency to differently allocate N when AMF or PGPR were used alone, pointed out the complexity of microorganism interaction and suggests the need for further investigations aimed at unraveling the mechanisms underlying this symbiosis.